Agriculture and Law in Japanese Society: Rolnictwo i prawo w społeczeństwie japońskim - Shimogaki, Shinji (Investigationes Linguisticae, 2020)
This study analyzes the changes in farmland system in Japan. The main policy of post-World War II Japan was regulation of the transfer lease or ownership of farmland, and the conversion of agricultural land into non-agricultural land considering the importance of farmlands. Paradoxically, this policy created some problems, such subdivision of farmland and ownerless lands. To address these problems, the Farmland Intermediary Management Institution was established in 2014 to accelerate farmland concentration and intensify the power of core farmers. In 2016, The Agricultural Land Act was reformed to make it easier for stock companies to own farmland. And, ICT has enabled us to visualize and verbalize tacit knowledge. This study explores the outcomes of these reforms and other unanswered issues.